Respostas
respondido por:
33
f ( x ) = 5 - x, essa é a função agora vamos descobrir suas imagem:
f ( 0 ) = 5 - 0 = 5
f ( 3 ) = 5 - 3 = 2
f ( - 2 ) = 5 - ( - 2 ) = 5 + 2 = 7
f ( 0 ) = 5 - 0 = 5
f ( 3 ) = 5 - 3 = 2
f ( - 2 ) = 5 - ( - 2 ) = 5 + 2 = 7
sisi2015:
valeu
respondido por:
9
Resposta:a) f (0)
f (x)=5-x
f (0)=5-0
f (0)=5
b) f (3)
f (x)=5-x
f (3)=5-3
f (3)=2
c) f (-2)
f (x)=5-x
f (-2)=5-(-2)
f (-2)=5+2
f (-2)=7
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás